Measuring accrued-to-date liabilities of public pension systems: Method, data and limitations - Matthias Heidler; Christoph Müller; Olaf Weddige (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2009)
This paper introduces the approach of the Freiburg model to quantify accrued-to-date liabilities (ADL) of public pension schemes. The presented framework has been applied to carry out benchmark calculations for 19 EU member states on behalf of the Eurostat/ECB Contact Group on Pensions. We will show that the Freiburg model represents a valuable instrument to calculate pension schemes' ADL on a relatively small data base. Furthermore, limitations and possible extensions of the model will be outlined.
Keywords: 330; Gesetzliche Rentenversicherung; Rentenfinanzierung; Versicherungstechnik; Rückstellung; Deutschland